FORMATIVE AND REFLECTIVE MODELS IN MARKETING RESEARCH - Claudia Ioana CIOBANU; Magdalena DANILEŢ (Management Intercultural, 2017)

(untitled)
Compliance with the construct validity criteria is necessary for the correct assessment of the research in terms of quality and for further development of the marketing models. The identification of formative and reflective constructs as well as the correct testing of their validity and reliability are important methodological steps for marketing research as described in this article. The first part defines the reflective and the formative constructs and highlighst their particularities by analysing the theoretical criteria that differentiate them. In the second part of the study aspects of validity and trust for the formative and reflective constructs are presented as well as some empirical considerations from research literature regarding their measurement.